Find the best solutions to your problems with the help of IDNLearn.com's expert users. Our experts provide timely and accurate responses to help you navigate any topic or issue with confidence.
Answer:
10
Step-by-step explanation:
to find the answer for 3y + 4 we have to find the value of y.
we can find that by using the second equation.
-2y+6=2
-2y+6-2 =0 (subtract 2 from both the sided)
4= 2y (we will bring the -2y to the other side of the equation and then subtract the 6-2 to get the 4)
4/2=y (divide by 2 on both the sides)
∴ y=2
now we will plug in the y of value that we see as -2 into the first equation.
∴ 3y+4 will become
= 3(2)+4
=6+4
=10
hope this helps!!